Use of immobilised lipase from Candida antarctica in supercritical fluid extraction of borage (Borago officinalis L.) seed oil - Venskutonis, Petras Rimantas; Daukšas, Egidijus; Sivik, Bjorn (2008)
This study aims at the investigation of the possibilities to use immobilised lipase from Candida antarctica in supercritical fluid extraction (SFE) of borage (Borago officinalis L.) seed oil. The first series of experiments was performed to measure the extract yields obtained with pure CO2 and with the added entrainer (ethanol). The yield increased more than twice after increasing the extraction pressure from 15 to 25 MPa. Further increase to 35 MPa was less effective. The effect of the entrainer was not significant in most cases. Palmitic (13.1-16.1 %), oleic (13.4-23.8 %), linoleic (33.8-48.4 %) and linolenic (8.8-16.3 %) acids were dominant in all extracted oils. Further experiments involved the use of enzyme. In this case the first extractor was loaded with ground borage seeds, the second one was filled with the enzyme. The total yield obtained at 15, 25 and 35 MPa was (8.8+/-0.2), (23.6+/-0.2) and (28.9+/-1.1) %, respectively. Thin layer chromatography (TLC) of fatty acid ethyl esters showed that the content of esters was higher in the extract obtained in one extractor system at 15 MPa, compared to 35 MPa.